Skin mucus metabolomics provides insights into the interplay between diet and wound in gilthead seabream (Sparus aurata). Issue 134 (March 2023) - Albaladejo-Riad, Nora; Espinosa-Ruiz, Cristóbal; Esteban, María Ángeles; Lazado, Carlo C.
Abstract: The molecular processes underlying skin wound healing in several fish species have been elucidated in the last years, however, metabolomic insights are scarce. Here we report the skin mucus metabolome of wounded and non-wounded gilthead seabream ( Sparus aurata ) fed with silk fibroin microparticles, a functional additive considered to accelerate the wound healing process. The three experimental diets (commercial diet enriched with 0 mg (control), 50 mg or 100 mg of silk fibroin microparticles Kg −1 ) were administered for 30 days and thereafter, a skin wound was inflicted. Skin mucus was collected on day 30 of feeding and 7 days post-wounding and subjected to metabolomic analysis by Ultra Performance Liquid Chromatography coupled with a high-resolution quadrupole-orbitrap mass spectrometry. The most enriched metabolite class was amino acids and derivatives, followed by nucleotides, nucleosides and analogues and carbohydrates and their derivatives. Metabolomic profiles revealed that the diet had a more profound effect than wounding in skin mucus. Metabolic pathway analysis of significantly affected metabolites revealed perturbations in the aminoacyl t-RNA biosynthesis in the skin. In particular, skin wound resulted in a decreased methionine level in mucus. Further, silk fibroin supplementation increased methionine level in skin mucus, which correlated with several wound morphometric parameters that characterized the epithelial healing capacity in seabream. The results provided new insight into the physiological consequences of skin wounds and how these processes could be influenced by dietary manipulation. Graphical abstract: Image 1 Highlights: First report on the skin mucus metabolome of wounded gilthead seabream. Skin mucus metabolome was influenced by diet and wound. Amino acids, nucleotides, nucleosides and carbohydrates were the enriched metabolite class. MetaBolites in aminoacyl t-RNA biosynthesis were significantly perturbed. Skin wound resulted in a decreased methionine level in skin mucus.